The Effect of E-Service Quality, Security, and Promotion on Customer Satisfaction of E-Commerce Shopee - I Gusti Ayu Wilya Susmitha Prami Dewi; Ni Luh Putu Surya Astitiani; Ni Made Widnyani (West Science Interdisciplinary Studies, 2024)
The rapid advancement of information technology has led to the convergence of telecommunications and computer technologies. This shift has also influenced consumer behavior, with a growing number of individuals becoming more accustomed to online shopping, resulting in an increasing number of e-commerce users. Shopee, the leading e-commerce platform in Indonesia, has the highest number of website visits, positioning it as the top e-commerce site in the country. The purpose of this study is to analyze how e-service quality, security, and promotions influence e-customer satisfaction with Shopee among Generation Z in Denpasar. The study employs a descriptive quantitative research method with a sample size of 100 respondents. The t-test results for e-service quality reveal a t-value of 5.930, which is greater than the critical value of 1.984, indicating a significant positive effect of e-service quality on customer satisfaction. Conversely, the security variable demonstrates a negative impact on customer satisfaction, with a t-value of -2.842, which is less than the critical value of 1.984. The promotion variable exhibits a positive effect on customer satisfaction, with a t-value of 4.916, exceeding the critical value of 1.984. Furthermore, the overall hypothesis is supported as the calculated F-value of 62.474 exceeds the F-table value of 2.70, indicating that e-service quality (X1), security (X2), and promotions (X3) collectively influence customer satisfaction (Y).